Kajian Perbandingan Raja Masa Klasik Sebagai Actor-Based Model Berdasarkan Data Epigrafi: Studi Kasus Raja Dapunta Hyang Sri Jayanasa Dan Sri Jayabhupati Jayamanahen - Muhamad Alnoza (Balai Arkeologi Provinsi Sulawesi Utara, 2020)
The actor-based model study is one of the environmental archaeological studies that focus on the interaction of an individual with the environment and its influence on culture. This study focuses on the study of actor-based models on figures of the kings of the classical period in Indonesia, which in this case takes the cases of Dapunta Hyang Sri Jayanasa and Sri Jayabupati Jayamanahen. To reconstruct how the two kings interacted with their environment, archaeological research methods based on inscription data were used. From a series of studies conducted it can be seen that Dapunta Hyang Sri Jayanasa is more successful in making adaptation strategies to its environment, while Sri Jayabupati is less successful. Dapunta Hyang Sri Jayanasa focuses on adaptation strategies in the development of Śrīkṣetra Park, while Sri Jayabupati focuses on prohibiting fishing on rivers in Kabuyutan Sang Hyang Tapak. Both have strategies that tend to meet the needs of their people.